2009
DOI: 10.1007/s00418-009-0639-4
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of P2X3 in vagal and spinal afferents following esophagitis in rats

Abstract: Purinergic P2X3 receptors are predominantly expressed in small diameter primary afferent neurons and activation of these receptors by adenosine triphosphate is reported to play an important role in nociceptive signaling. The objective of this study was to investigate the expression of P2X3 receptors in spinal and vagal sensory neurons and esophageal tissues following esophagitis in rats. Two groups of rats were used including 7 days fundus-ligated (7D-ligated) esophagitis and sham-operated controls. Esophagiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…Purinergic receptors of the P2X family (Xu et al, 2008;Banerjee et al, 2009;Hsieh et al, 2012), and acidsensing ion channels (ASICs) are expressed in sensory neurons of the DRG and were suggested to be involved in mechanical pain perception (Price et al, 2000. For nociception Asic2a and Asic3a are of particular interest as both are expressed by smalldiameter DRG neurons (García-Añoveros et al, 2001;Duggan et al, 2002).…”
Section: Ngr2 Does Not Affect the Expression Of Skin-derived Growth Fmentioning
confidence: 99%
“…Purinergic receptors of the P2X family (Xu et al, 2008;Banerjee et al, 2009;Hsieh et al, 2012), and acidsensing ion channels (ASICs) are expressed in sensory neurons of the DRG and were suggested to be involved in mechanical pain perception (Price et al, 2000. For nociception Asic2a and Asic3a are of particular interest as both are expressed by smalldiameter DRG neurons (García-Añoveros et al, 2001;Duggan et al, 2002).…”
Section: Ngr2 Does Not Affect the Expression Of Skin-derived Growth Fmentioning
confidence: 99%
“…Similar to other studies reporting P2X3 receptor expression in vagal sensory cell bodies using immunohistochemical techniques we also found that P2X3 receptors were highly prevalent and distributed throughout the NG (Banerjee et al, 2009a, Wang et al, 2014. These findings suggest that a large population of vagal afferents are sensitive to ATP and thus through purinergic signaling mechanisms, serve an important role in mechanosensory transduction.…”
Section: Immunohistochemical Phenotype Of Ng Neuronssupporting
confidence: 78%
“…However, SCI does lead to pathological changes and dysfunction of below-level target organs, such as the bladder (de Groat et al, 1990, Kruse and de Groat, 1993, and can thereby influence neuronal phenotype (Vizzard, 1997, Yoshimura et al, 1998, Vizzard, 1999, Yoshimura, 1999, Vizzard, 2000a, Qiao and Vizzard, 2002, Zvarova et al, 2004, Qiao and Vizzard, 2005, Zvarova et al, 2005, Zvara et al, 2006. Furthermore, various classes of primary sensory neurons, including vagal afferents, have been shown to alter their phenotype and 51 the expression of different receptors in response to nerve injury and tissue inflammation (Murphy et al, 1995, Neumann et al, 1996, Li et al, 1999, Michael and Priestley, 1999, Banerjee et al, 2009a, Banerjee et al, 2009b, Hill et al, 2010. In this study, we examined the effects of SCI on the neurochemistry of the NG.…”
Section: Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies documented upregulation of the P2X3 purinoceptor in peripheral neuropathic pain, for example in mechanical injury-induced focal neuropathy [4], in a chronic visceral pain model [5,6], and in chemotherapy-induced neuropathy [7]. The roles of P2X3 activation in neuropathic pain were confirmed by functional blockade [8][9][10] and by administering exogenous ATP, which evokes pain behaviors [11,12].…”
Section: Introductionmentioning
confidence: 83%